2021
DOI: 10.1097/md.0000000000023975
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and cardiovascular mortality in patients with atrial fibrillation

Abstract: Our aim was to analyze characteristics of atrial fibrillation (AF) patients with chronic kidney disease (CKD) from the Croatian cohort of the ESH A Fib survey and to determine the association of estimated glomerular filtration rate (eGFR) with cardiovascular (CV) mortality after 24 months of follow-up. Consecutive sample of 301 patients with AF were enrolled in the period 2014 to 2018. Hypertension was defined as BP > 140/90 mm Hg and/or antihypertensive drugs treatment, CKD was defined as eGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
5
0
2
Order By: Relevance
“…Results provided evidence for the significantly better performance of GFR-based schemes—R2(GFR)CHADS2 and R2(GFR)CHA2DS2VASc—and the moderately better performance of CrCl-based schemes—R2(CrCl)CHADS2 and R2(CrCl)CHA2DS2VASc—in death risk stratification compared with CHADS2 and CHA2DS2VASc scores [ 32 ]. These findings, however, were not confirmed in a recent study by Premuzic et al The investigators sought to determine the association of eGFR with CV mortality in AF patients after 24 months of follow-up [ 33 ]. They concluded that CV mortality was independently associated with eGFR ( b = 0.169, P = 0.04), male gender ( b = 0.156, P = 0.03), CHA2DS2VASc ( b = 0.467, P = 0.02) and R2CHA2DS2VASc scores ( b = 0.391, P = 0.04) but not with R2CHADS2 score.…”
Section: Cha2ds2vasc and R2chads ± Vasc Score In Atrial Fibrillation Patients With Chronic Kidney Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…Results provided evidence for the significantly better performance of GFR-based schemes—R2(GFR)CHADS2 and R2(GFR)CHA2DS2VASc—and the moderately better performance of CrCl-based schemes—R2(CrCl)CHADS2 and R2(CrCl)CHA2DS2VASc—in death risk stratification compared with CHADS2 and CHA2DS2VASc scores [ 32 ]. These findings, however, were not confirmed in a recent study by Premuzic et al The investigators sought to determine the association of eGFR with CV mortality in AF patients after 24 months of follow-up [ 33 ]. They concluded that CV mortality was independently associated with eGFR ( b = 0.169, P = 0.04), male gender ( b = 0.156, P = 0.03), CHA2DS2VASc ( b = 0.467, P = 0.02) and R2CHA2DS2VASc scores ( b = 0.391, P = 0.04) but not with R2CHADS2 score.…”
Section: Cha2ds2vasc and R2chads ± Vasc Score In Atrial Fibrillation Patients With Chronic Kidney Diseasementioning
confidence: 98%
“…They concluded that CV mortality was independently associated with eGFR ( b = 0.169, P = 0.04), male gender ( b = 0.156, P = 0.03), CHA2DS2VASc ( b = 0.467, P = 0.02) and R2CHA2DS2VASc scores ( b = 0.391, P = 0.04) but not with R2CHADS2 score. In addition, R2CHA2DS2VASc was not associated with CV mortality more than CHA2DS2VASc [ 33 ].…”
Section: Cha2ds2vasc and R2chads ± Vasc Score In Atrial Fibrillation Patients With Chronic Kidney Diseasementioning
confidence: 99%
“…The importance of reducing renal function decline and the potential impact of the choice of anticoagulant on renal outcomes in patients with AF have also been highlighted in the 2019 update to the American College of Cardiology/American Heart Association/Heart Rhythm Society guidelines on the management of AF, stating that ‘over time, NOACs (particularly dabigatran and rivaroxaban) may be associated with lower risks of adverse renal outcomes than warfarin in patients with AF’ [ 31 ]. This is particularly relevant in patients with AF and diabetes given the impact of worsening GFR on mortality and CV death [ 31 , 112 , 113 ]. Thus, in the context of comprehensive preventive strategies in this very vulnerable population, warfarin is not the preferred anticoagulant at an early stage in patients with diabetes, AF or in the early stages of diabetic renal disease.…”
Section: Considering Renal Impairment In Thromboembolic Prevention St...mentioning
confidence: 99%
“…The optimal cutoff point of CHA 2 DS 2 -VASc was 3 and MCHA 2 DS 2 -VASc was 8 for predicting the incidence of recurrent MI, which was determined by receiver operating characteristic (ROC) curve, area under the curve (AUC) analysis, and Youden index. Patients were subsequently categorized into the low-risk group (0-2) and high-risk group (3)(4)(5)(6)(7)(8)(9) according to the CHA 2 DS 2 -VASc and low-risk group (0-7) and high-risk group (8)(9)(10)(11)(12)(13)(14)(15) according to the MCHA 2 DS 2 -VASc.…”
Section: Definitions and Outcome Measuresmentioning
confidence: 99%
“…Many clinical stroke risk factors (e.g., obstructive sleep apnea, left atrium dilatation, and renal impairment) ( 6 8 ) as well as some biomarkers (e.g., troponin, natriuretic peptides, and von Willebrand factor) ( 9 , 10 ) are closely related to the stroke risk, but they do not improve the predictive value of CHA 2 DS 2 -VASc score. Moreover, patients with MI seem to be at increased risk for recurrent major adverse cardiovascular events (MACEs), owing to their clinical characteristics, comorbidities, and biomarkers, such as elderly (especially older women) ( 11 ), diabetes mellitus (DM), heart failure (HF), renal dysfunction ( 12 ), and interleukin-1beta ( 13 ).…”
Section: Introductionmentioning
confidence: 99%